Faktor-Faktor Yang Memengaruhi Kebijakan Dividen Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Galang Dwi Saputro; Aditya Hermawan (Program Studi Akuntansi PSDKU Universitas Pattimura, 2021)
This study aims to determine the effect of managerial ownership, institutionalownership, sales growth, and firm size on dividend policy. The object of this researchis the food and beverage sector manufacturing companies listed on the Indonesia StockExchange for the period 2017-2019. The research population is a manufacturingcompany in the food and beverage sector in 2017-2019. According to Bahri (2018;51)the sample is part of the population taken from certain ways that also have certaincharacteristics. The method of determining the research sample is purposive sampling.Purposive sampling is a sample selection technique based on certain criteria with theaim of providing maximum information (Bahri, 2018; 66). The existence of institutionalownership serves to monitor the performance of management by outsiders, while theportion of managerial ownership which is also a shareholder tries to maximize itsperformance. The growth of the sales rate shows that the company's profit is increasing.Dividends distributed to investors come from the company's profits so that withincreased sales, the profits earned by the company also increase and the dividendsdistributed also increase. The size of the company is accepted, which means that thesize of the company affects the dividend policy.